(untitled) (Bangladesh Journal of Medicine, 2022)
Subacute thyroiditis is an immune reaction of the thyroid gland that often follows an upper respiratory tract infection. It is an uncommon but usually a self-limiting inflammatory condition. The clinical presentation varies from person to person, but usually includes neck pain or discomfort and a painful diffuse goiter. There is at times a transient episode of hyperthyroidism followed by euthyroidism and sometimes hypothyroidism. We describe the case of a previously healthy 34- year-old female presenting with symptoms consistent with subacute thyroiditis. The patient had recently recovered from a mild episode of COVID-19 infection. Labs and imaging were consistent with the clinical diagnosis of subacute thyroiditis. The patient was provided symptomatic treatment with prednisone and propranolol and had an uneventful recovery. Bangladesh J Medicine 2022; 33: 210-212